2021
DOI: 10.3389/fmicb.2021.682290
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Function of Lactobacillus fermentum MF423-Fermented Rice Bran and Its Effect on Gut Microbiota Structure in Type 2 Diabetic Mice

Abstract: Rice bran is an industrial byproduct that exerts several bioactivities despite its limited bioavailability. In this study, rice bran fermented with Lactobacillus fermentum MF423 (FLRB) had enhanced antidiabetic effects both in vitro and in vivo. FLRB could increase glucose consumption and decrease lipid accumulation in insulin resistant HepG2 cells. Eight weeks of FLRB treatment significantly reduced the levels of blood glucose and lipids and elevated antioxidant activity in type 2 diabetic mellitus (T2DM) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 64 publications
1
43
0
1
Order By: Relevance
“…Furthermore, lipocalin 2, an antimicrobial peptide expressed in the intestine, modulated obesity-associated and metabolic dysregulation through SCFA production regulated by Dubosiella and Angelakisella 43 . In addition, enriched Dubosiella in fermented rice bran–treated mice improved insulin sensitivity, antioxidative capacity, and lipid levels 44 . In another study, Faecalibaculum and its homology, Holdemanella biformis , demonstrated intestinal antitumorigenic effects through the production of SCFAs, which controlled the protein acetylation and tumor cell proliferation underlying calcineurin inhibition and NFATc3 activation 45 .…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, lipocalin 2, an antimicrobial peptide expressed in the intestine, modulated obesity-associated and metabolic dysregulation through SCFA production regulated by Dubosiella and Angelakisella 43 . In addition, enriched Dubosiella in fermented rice bran–treated mice improved insulin sensitivity, antioxidative capacity, and lipid levels 44 . In another study, Faecalibaculum and its homology, Holdemanella biformis , demonstrated intestinal antitumorigenic effects through the production of SCFAs, which controlled the protein acetylation and tumor cell proliferation underlying calcineurin inhibition and NFATc3 activation 45 .…”
Section: Discussionmentioning
confidence: 96%
“…When supplemented with FRB, liver damage was alleviated as described by significantly lower NAFLD scores and liver IL-1β levels, and slightly lower levels of liver TNF-α and plasma TBARSs ( Figure 4 , Table 2 , Table 3 and Table 4 ). Likewise, Ai et al found that FRB could mitigate hepatic steatosis in mice with type 2 diabetes mellitus (T2DM) [ 35 ]. Lipid accumulation was also improved by FRB treatment in IR-HepG2 cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ai et al found that FRB could mitigate hepatic steatosis in mice with type 2 diabetes mellitus (T2DM) [ 35 ]. Lipid accumulation was also improved by FRB treatment in IR-HepG2 cells [ 35 ]. In a mouse model of obesity, it was reported that supplementation with FRB could decrease fatty depositions in liver tissues [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations